Application of Pulp Fiber for Automotive Brake Lining - Wawan Kartiwa Haroen; Posma Reginald Panggabean (Wood Research Journal, 2012)
Mechanical and/or chemical pulp fiber is usually used for papermaking and other kind of paper products. In fact, physical properties of chemical and/or mechanical pulp showed that it can be utilized as filler of automotive brake lining.  Mechanical pulp is non-asbestos cellulosic fiber with high heat absorption rate which can fit into criterion of good quality brake lining. Pulp  fiber was defiberation mixed with some other composite materials can create high fiber bonding with some hardness, friction materials, clutching, heat and dust retainer fiber which is free of asbestos fiber. Current automotive brake lining uses asbestos fiber as main filler, which is in fact known as cancer triggers.  A series of study and assessment in using pulp fiber in a specified composition as brake lining filler have been carried out. The research and field experiment revealed that a mixture of pulp fiber can be further examined and feasible for brake lining prototype filler application which is ready for automotive vehicles operation. The development and application fiber brake lining filler has been tested on two wheeled vehicles with considerable result.